Pendidikan Profesi Guru dan Peningkatan Mutu Pendidikan - Naf’an Tarihoran (Jurnal keilmuan dan Kependidikan dasar, 2012)
The purpose of this paper is to briefly introduce and study of teachers professional education towards quality assurance of education. The formal education system in Indonesia is in a state of great transformation. The national education law of 2003 calls for an increase in quality and mandates that standards be developed and codified in the following areas: The Content of Education, The Process of Education, Facilities and Infrastructure, Management, Teachers and Education Staff, The Financing of Education, Standard of Graduates from Education, Evaluation of Schools and other Education Units. The Government of Indonesia has made great strides in developing these standards especially with regards to teachers. Law 19 /2003 on the National Education Standards, Law 14/2005 on the Teacher and Lecturer, the Regulation from the Minister of National Education No16/2007 on Teacher Competency Standards, and the Regulation from the Minister of National Education No 18/2007 on the Certification for Teachers detail the minimum qualifications and competencies teachers are expected to possess and the process of assessment. The Ministry of National Education and in particular the Directorate General for the Quality Improvement of Teachers and Education Personnel and the Directorate General for Higher Education are now faced with the enormous task of ensuring that 3,000,000 teachers already in service and all newly qualified teachers meet these standards. This is by no means an easy task in a country as diverse and large as Indonesia. To enable both lecturers and students to achieve National standards of education, therefore, Teacher training institution (LPTK) should be prepared for and designed its curriculum comprehensively.